Konsep Perjanjian Profit and Loss Sharing dalam Ekonomi islam - Fahrurrozi Fahrurrozi (Institut Agama Islam Negeri Madura, 2016)
Agreements of Profit and Loss Sharing is an agreement based on the confidence (trust investment), in another sense that financiers or Shahibul Mall will deliver the funds to the fund manager or mudharib after investors feel confident that the managers of these funds both skill and moral can be trusted to manage the capital provided by the expertise and capital will not manipulate it. With this fact it is necessary to examine the concept of profit and loss sharing agreement, with the hope to find a concept that is based on the teachings of Islam. In this paper presents about the concept of Profit and Loss Sharing in the view of Islamic economics is based on the Qur'an and Hadith.